2015
DOI: 10.1038/srep09921
|View full text |Cite|
|
Sign up to set email alerts
|

Conceptualization and validation of an open-source closed-loop deep brain stimulation system in rat

Abstract: Conventional deep brain stimulation (DBS) applies constant electrical stimulation to specific brain regions to treat neurological disorders. Closed-loop DBS with real-time feedback is gaining attention in recent years, after proved more effective than conventional DBS in terms of pathological symptom control clinically. Here we demonstrate the conceptualization and validation of a closed-loop DBS system using open-source hardware. We used hippocampal theta oscillations as system input, and electrical stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The reason is that closed-loop devices deliver electrical stimulation based on the state of the brain. Therefore, these devices remain less active over a course of time which results in a reduction of the electrical energy delivered to the brain [ 4 ]. However, closed-loop devices have extra recording and processing circuits that could increase the overall power consumption of the device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that closed-loop devices deliver electrical stimulation based on the state of the brain. Therefore, these devices remain less active over a course of time which results in a reduction of the electrical energy delivered to the brain [ 4 ]. However, closed-loop devices have extra recording and processing circuits that could increase the overall power consumption of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients may also benefit from fewer surgeries for replacement of the neurostimulator battery as a result of less power consumption in non-continuous stimulations [ 3 ]. Little et al [ 3 ] and Wu et al [ 4 ] reported that in order to obtain similar results from open-loop and closed-loop DBS, 44% less electrical stimulation is required using closed-loop DBS, which means higher efficiency, fewer surgery numbers, lower power consumption, and longer battery lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…We used a wired, current-controlled stimulation system (STG 4008, Multi Channel Systems MCS GmbH, Reutlingen, Germany) and examined biphasic pulse-shapes with interphase gaps of 0 µs (standard biphasic pulse, BP), 60 µs (IPG60) and 120 µs (IPG120). Frequency and pulse width were set at 130 Hz and 60 µs, respectively, based on a previous study performed by our research group 19 . Stimulation amplitudes were gradually increased in 25 µA steps, to avoid acute behavioral side effects.…”
Section: Methodsmentioning
confidence: 99%
“…A major DBS manufacturer has demonstrated a Bsensing^system that can record from the human brain and provide those signals to clinicians [117] and has proven that it can be used for closedloop control in an epilepsy-like application [118•, 119]. On the animal side, several groups have demonstrated open hardware platforms that can readily be customized to enable closed-loop control of brain activity with commodity parts [120][121][122], and a system resembling those was successfully used for closedloop control of psychiatrically relevant brain areas in rodents [123•]. Biomarkers are the greater challenge.…”
Section: Responsive Closed-loop Stimulationmentioning
confidence: 99%